MENGAPA MASYARAKAT ENGGAN MEMBAYAR PAJAK - Tulis S. Meliala (Bina Ekonomi, 2007)
Tax, based on society's opinion, is not comfortable  thing and  like a frightfull thing. ln matter of paying  tax to the government,  most people don't have the willingness to do so because  people don't have an Understanding about  tax, there are rumours among entrepreneurs  that  tax can make  their companies  ,broke, and people  don’t  receive benefit of paying  tax.  lf the society have an understanding about  tax and  its history and the reason of paying tax, than  tax should no longer became a frightfull thing,  instead  the society must feel  the responsibility  tor paying taxKey word:  lncome Tax;  Value Added Tax